Pemetaan Sebaran Jenis Mangrove Menggunakan Citra Drone dengan Metode Object-Based Image Analysis (OBIA) di Sungai Pisang, Kecamatan Bungus Teluk Kabung, Kota Padang - Irsal, Mursyid; Syarief, Azhari (MASALIQ, 2024)
This research has purpose to find out what types of mangroves and factors affect the distribution of mangroves in Sungai Pisang, Bungus Teluk Kabung District, Padang City. The research method used is quantitative research. The data used is primary data such as drone imagery. The results of this research produced seven types of mangroves and factors the distribution of mangrove types. The types of mangroves found were Rizhophora apiculate, Oncomsperma tigillarium, Ceriops tagal, Bruguiera gymnorhiza, Hibiscus tiliaceus, Acrostichum aureum linn, Sonneratia alba. Meanwhile, there are three factors that influence the distribution of mangroves, namely Substrate, Salinity and Soil Texture. The dominant substrates are muddy and sandy substrates, the lowest salinity is 12ppt and the highest is 30ppt, while the dominant soil textures are clay, clay and sandy.